Reflections on the Dangers and Delusions of Education Tourism for Educational Development in Nigeria. - Nyewusira, Benjamin. N.; Nyewusira, Chituru (Archives of Business Research, 2021)
In contemporary times, education tourism has become such a complex phenomenon vis-à-vis the overall development of education in Nigeria. This paper, after explaining the concept of education tourism, takes into consideration the initial historical imperatives that occasioned the need for Nigerians to travel overseas for Higher Education. It identifies the challenges that prompted a rise in education tourism, noting that the Nigerian education sector in particular, and the Nigerian nation in general, suffers huge capital flights as a result of this phenomenon. A further critical analysis from the paper shows that the recent incidents and experiences with education tourism live some Nigerian students with many dangers and delusions-the delusions arising from the incongruence between the knowledge acquired abroad and the dysfunctional social systems in Nigeria. Consequently, the paper submits that Nigerians will be speared much of the complex problems identified with education tourism if the country can adopt some immediate and remote measures that will revitalize its education and make it attractive to the rest of the globe.